2016
DOI: 10.1002/adsc.201501101
|View full text |Cite
|
Sign up to set email alerts
|

Property‐Guided Synthesis of Aza‐Tricyclic Indolines: Development of Gold Catalysis En Route

Abstract: Antibiotic resistance is a worldwide public health threat that needs to be addressed by improved antibiotic stewardship and continuing development of new chemical entities to treat resistant bacterial infections. Compounds that work alongside known antibiotics as combination therapies offer an efficient and sustainable approach to counteract antibiotic resistance in bacteria. Guided by property-based analysis, a series of aza-tricyclic indolines (ATIs) were synthesized to optimize their physiochemical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Further biological profiling studies showed that some hits from the screens, such as the ring-opened fused indoline Of1 ( 1 , Figure 1) and tetracyclic indolenine 2, selectively re-sensitizes MRSA to β-lactam antibiotics [33]. Aza-tricyclic indoline 3 (Figure 1) was developed to optimize the physiochemical properties Of1 [39]. Herein, we report the antibiotic profiling and structure-activity relationship (SAR) studies of alkylated fused indoline Kf18 ( 4 , Figure 1), another hit compound from our previous screens [33], with a distinct tetracyclic indoline scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Further biological profiling studies showed that some hits from the screens, such as the ring-opened fused indoline Of1 ( 1 , Figure 1) and tetracyclic indolenine 2, selectively re-sensitizes MRSA to β-lactam antibiotics [33]. Aza-tricyclic indoline 3 (Figure 1) was developed to optimize the physiochemical properties Of1 [39]. Herein, we report the antibiotic profiling and structure-activity relationship (SAR) studies of alkylated fused indoline Kf18 ( 4 , Figure 1), another hit compound from our previous screens [33], with a distinct tetracyclic indoline scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…The rationalized mechanism of this tandem cyclization process involves π‐activation, nucleophilic indole addition in 6‐ exo‐dig mode and second nucleophilic amine addition to the iminium intermediate followed by subsequent protodeauration (Scheme 83). [97] …”
Section: Metamorphosis Of Heteroarene‐tethered Propargyl Amines and Tmentioning
confidence: 99%
“…The rationalized mechanism of this tandemc yclization process involves p-activation, nucleophilic indole addition in 6-exo-dig mode and second nucleophilic amine additiont ot he iminium intermediate followed by subsequentprotodeauration (Scheme 83). [97] In 2018, Maestri and co-workers developed ap rotocol for the synthesis of tetrahydro-b-carbolines from the corresponding N-propargyl tryptamines jointly catalyzed by Pd 0 and benzoic acid. Treatment of tryptamined erivative 332 with 5mol % Pd(PPh 3 ) 4 and 30 mol %b enzoic acid furnished the desired carboline derivatives 334 in good yields.…”
Section: Scheme73mentioning
confidence: 99%
“…24,25 It is worth mentioning that another gold-catalyzed cyclization was developed to facilitate the synthesis of the aza-tricyclic indoline core structure of 1 for further inquiry. 26 This study yielded compound 2, which had greatly improved pharmacokinetic properties and water solubility compared to 1. 26 These properties were desired because the biological profile and poor water solubility of 1 had prevented it from use in animal studies.…”
Section: Scheme 3 Modifications Of Cyclized Products Such As Reductive Ring Opening Yield Various Additional Scaffolds 3 Chemical Probe Dmentioning
confidence: 99%
“…26 This study yielded compound 2, which had greatly improved pharmacokinetic properties and water solubility compared to 1. 26 These properties were desired because the biological profile and poor water solubility of 1 had prevented it from use in animal studies. Ongoing synthesis and testing of indole alkaloid-like compounds revealed other structures that exhibited RMA activity against MRSA, such as compound 3, which was discovered from a collection of bridged tetracyclic indolenines.…”
Section: Scheme 3 Modifications Of Cyclized Products Such As Reductive Ring Opening Yield Various Additional Scaffolds 3 Chemical Probe Dmentioning
confidence: 99%